2019
DOI: 10.7600/jpfsm.8.229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined therapy of ACE inhibitor and exercise on cardiovascular functions and morphology of the heart and kidneys in SHR

Abstract: An exercise regimen rarely causes organ damage in humans or rats with established essential hypertension. However, daily exercise is essential for elderly people to prolong a healthy lifespan. This study was designed to examine the effects of exercise training alone and the combined treatment of exercise and anti-hypertensive medication on morphological characteristics of the heart and kidneys, as well as to examine the response to pressor agents in the spontaneously hypertensive rat (SHR). SHRs were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Therefore, to obtain stable levels, OGTT was performed under diethyl ether anesthesia. Approximately 500 μL blood was obtained from the retro-orbital sinus 4,5,26) immediately before and at 30, 60, and 120 min after oral administration of glucose (2 g/kg BW). The BG concentrations were measured at these times (Glucose C II-test; Wako Pure Chemical Industries), and area under the BG concentration-time curve (AUCglucose) was calculated 1) .…”
Section: Measurement Of Bw Bp and Fcmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, to obtain stable levels, OGTT was performed under diethyl ether anesthesia. Approximately 500 μL blood was obtained from the retro-orbital sinus 4,5,26) immediately before and at 30, 60, and 120 min after oral administration of glucose (2 g/kg BW). The BG concentrations were measured at these times (Glucose C II-test; Wako Pure Chemical Industries), and area under the BG concentration-time curve (AUCglucose) was calculated 1) .…”
Section: Measurement Of Bw Bp and Fcmentioning
confidence: 99%
“…The right kidney of each rat was halved longitudinally, placed in 20% formalin for 1 week, and embedded in paraffin. Paraffin sections stained with periodic acid silver methenamine were used to determine glomerular size as previously described [4][5][6]30) . The glomerular and mesangial areas [A(G) and A(M), respectively] were measured using an automatic image analyzer (Olympus SP-500; AVIO, Tokyo, Japan) fitted onto a microscope [4][5][6]30) .…”
Section: Renal Morphological Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Ishaq et al [ 13 ] reported that dietary restriction ameliorates the level of senescence-related markers, such as p16 and p21, in the visceral adipose tissue of comparatively aged mice (17.5-month-old mice). Similarly, regular exercise, with or without using a free-running wheel, decreases visceral fat volume [ 14 , 15 , 16 , 17 , 18 ]. Exercise is well known to protect against the development of fat cell hypertrophy and insulin resistance [ 19 ].…”
Section: Introductionmentioning
confidence: 99%